Open market repurchase program, dividend payment status, information asymmetry, and institutional ownership - Hội thảo quốc tế Ngân hàng và Tài chính thế giới 2015 (Trường Đại học Kinh tế, 2020)
This study examines the information content of open market share repurchase (OMR) announcements while taking into account the firm’s dividend payment status. We find that the market reacts more positively to the OMR announcements by non-dividend paying firms than to those by dividend paying firms. Among dividend paying firms, we find a stronger market reaction to the OMR announcements by firms having no changes in their dividend payments. We also document that dividend status mitigates the effect of information asymmetry caused by ownership structure of repurchase firms. In addition, the market has reacted less positively to the OMR announcements after the 2003 tax cut.